Expediente v.19 (2021) - Beck, Ana Lucia (Visualidades, 2022)
Visualidades, v. 19(2021): Equipe Editorial Ana Lúcia Beck (FAV/UFG) - Editora Chefe Paulo Henrique Duarte-Feitoza (FAV/UFG) - Editor Chefe Dustan Oeven (FAV/UFG) – Apoio Editorial Marina Muniz Mendes (FAV/UFG) – Apoio Editorial Mariana Capeletti (FAV/UFG) – Apoio Editorial Marilia Gontijo de Macedo (FAV/UFG) - Apoio Editorial Comunicação Institucional Emmanuel Felipe Araújo de Amaral (Badu) (FAV/UFG) Thaysa Alarcão Lemos (FAV/UFG)